Nonlocal vibrations of shell-type CNT conveying simultaneous internal and external flows by considering slip condition - Mirramezani, Mehran; Mirdamadi, Hamid Reza; Ghayour, Mostafa (Computer methods in applied mechanics and engineering, 2014)
•Analyze nonlocal vibration of shell-type CNT subject to internal and external flow.•Kn and nonlocal parameters decrease the eigen-frequencies and divergence velocity.•Kn has more contribution than nonlocality to reduce critical velocity of gas flow.•External flow reduces critical velocity of CNT conveying internal/external flow.•Denser external flow results in more decline in critical velocity/eigen-frequency. In this article, the nonlocal but linear vibrations of carbon nano-tubular shells are analyzed subjected to both internal and external flows. This analysis is addressed for both separate flows as well as concurrent flows by considering slip condition. We observe that both nonlocal parameter and Kn could decrease the eigen-frequency and critical velocity of the first-mode divergence. It is observed that the existence of quiescent fluid does not impress the value of divergence velocity. Nonetheless, the frequencies are declined substantially. Besides, we perceive that CNT subjected to both internal and external flows loses its stability drastically sooner as compared with that subjected to each flow separately. Furthermore, it is observed that an increase in the value of mass density of the external flow results in a greater decrease in the eigen-frequencies as well as the divergence velocity.